Ecologia alimentar de Tatu-Peba, Euphractus sexcinctus (Linnaeus, 1758), na Fazenda Nhumirim, Pantanal da Nhecolância, MS - Zambrini, Ana Carolina Vasques [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Studies on feeding ecology are important tools for the understanding of feeding strategies and niche dynamics. Information on the type of food consumed, how, and where it is acquired, enable the elucidation of species behavioral, evolutionary and ecological aspects. The diet study based on fecal material enables a low-cost, informative research and avoids the sacrifice of animals. The general aim of this study is to characterize the diet of Euphractus sexcinctus, the yellow-armadillo, based on fecal samples, to contribute with additional information on their feeding habits. The study was undertaken at the Nhumirim ranch, Pantanal da Nhecolândia, MS, during the months of February and March, 2014. The fecal material was collected during the manual capture of the animals and oven dried at 60°C. The food items found in the feces were sorted using a magnifying glass and separated in the following categories: plant matter, invertebrates and soil. Invertebrates were identified to the order level and the plant matter to the lowest taxonomic level possible. Aiming to evaluate the invertebrate availability in the soil, pitfall traps were installed next to the location where individuals were captured, during the months of April and May. We were able to estimate the frequency with which item was consumed during the studied period, and if there is a relationship between the frequency of consumed invertebrates and their availability environment. Among the analyzed samples, we could observe the frequency of occurrence (FO) of plant matter, invertebrates and soil in all the samples. The main invertebrate orders found in the samples were: Coleoptera, Orthoptera and Hymenoptera, with FO of 100%, 100% and 87,5%, respectively. Seeds were found in 100% of the samples. The FO of the Byrsonima orbignyana was high (62,5%), and evidences the potential of the yellow-armadillos as seed dispersers. The use of other techniques, such as the micro-histological...

Estudos de ecologia alimentar são importantes ferramentas para conhecer as estratégias de alimentação e compreender a dinâmica de nicho. Informações acerca do tipo de alimento consumido, como e onde este é obtido, tornam possível a elucidação de aspectos comportamentais, evolutivos e ecológicos das espécies. O estudo da dieta baseado em material fecal possibilita uma pesquisa informativa, de baixo custo e evita o sacrifício de animais. O objetivo geral deste trabalho foi caracterizar a dieta de Euphractus sexcinctus, tatu-peba, a partir de amostras de fezes, a fim de contribuir com informações sobre seus hábitos alimentares. Este estudo foi realizado na Fazenda Nhumirim, Pantanal da Nhecolândia, MS, durante os meses de fevereiro e março de 2014. O material fecal foi coletado durante a captura manual de indivíduos da espécie e seco em estufa a 60°C. Os itens alimentares encontrados nas fezes foram triados com auxílio de lupa e separados nas seguintes categorias: matéria vegetal, invertebrados e solo. Os invertebrados foram identificados até o nível de ordem e a matéria vegetal até o menor nível taxonômico possível. Com o objetivo de avaliar a disponibilidade de invertebrados, armadilhas de queda foram instaladas próximas aos pontos de captura dos indivíduos, durante os meses de abril e maio. Foi possível avaliar a frequência de ocorrência com que cada item alimentar foi consumido durante o período em questão, e se existe relação entre a frequência de invertebrados consumidos e a sua disponibilidade no ambiente. Dentre as amostras analisadas foi possível observar a frequência de ocorrência (FO) de material vegetal, invertebrados e partículas de solo em todas as amostras. As principais ordens de invertebrados consumidas foram: Coleoptera, Orthoptera e Hymenoptera, com FO de 100%, 100% e 87,5%, respectivamente. Sementes foram encontradas em 100% das amostras. A FO de Byrsonima orbignyana foi alta (62,5%)...
Keywords: Ecologia animal; Tatu; Animais - Alimentos; Habitos alimentares; Pantanal da Nhecolândia (MS)